PEMBANGUNAN KERETA CEPAT JAKARTA-BANDUNG SEBAGAI MERCUSUAR HUBUNGAN INDONESIA-TIONGKOK - Yamin, Muhammad; Windymadaksa, Shellia (JPP (Jurnal Politik Profetik), 2017)
Cooperation between Indonesia and China after President Joko Widodo elected in 2014 is felt increasingly intense and closely, it can be seen on the many bilateral cooperation conducted by both countries. In particular, the construction of the Jakarta-Bandung Rapid Train is a project that receives more attention in the Indonesian-China partnership. This is because projects estimated to spend around 60-90 trillion rupiahs are mega projects in bilateral cooperation between the two countries. The construction of the Jakarta-Bandung Rapid Train does not use APBN funds but through the B to B scheme (Business to Business) is a new breakthrough in the implementation of a mega project. Moreover, the rapid development cooperation of Jakarta-Bandung train is a guarantee for the improvement of Indonesia's status as an investment-friendly country, so that in the future investors will be more confident in the easiness, security and comfort of investing in Indonesia.